2010
DOI: 10.1016/j.ydbio.2010.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Maternally and zygotically provided Cdx2 have novel and critical roles for early development of the mouse embryo

Abstract: Divisions of polarised blastomeres that allocate polar cells to outer and apolar cells to inner positions initiate the first cell fate decision in the mouse embryo. Subsequently, outer cells differentiate into trophectoderm while inner cells retain pluripotency to become inner cell mass (ICM) of the blastocyst. Elimination of zygotic expression of trophectoderm-specific transcription factor Cdx2 leads to defects in the maintenance of the blastocyst cavity, suggesting that it participates only in the late stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 31 publications
5
85
1
Order By: Relevance
“…Our results, derived from CDX2-knockdown porcine embryos, indicate that CDX2 is not essential before blastocyst formation, since the siCDX2 blastocyst rate was no different from that of the control. This result is consistent with several studies in mice, which show that Cdx2-mutant or knockdown (Wu et al, 2010) embryos develop normally to the blastocyst stage; however, others have found that Cdx2 depletion induces developmental arrest before blastocyst formation (Jedrusik et al, 2010(Jedrusik et al, , 2015. Different time points for CDX2 accumulation in mice and other mammals might account for the different phenotypes of CDX2-depleted mouse and pig embryos.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results, derived from CDX2-knockdown porcine embryos, indicate that CDX2 is not essential before blastocyst formation, since the siCDX2 blastocyst rate was no different from that of the control. This result is consistent with several studies in mice, which show that Cdx2-mutant or knockdown (Wu et al, 2010) embryos develop normally to the blastocyst stage; however, others have found that Cdx2 depletion induces developmental arrest before blastocyst formation (Jedrusik et al, 2010(Jedrusik et al, , 2015. Different time points for CDX2 accumulation in mice and other mammals might account for the different phenotypes of CDX2-depleted mouse and pig embryos.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Cdx2-deficient blastomeres allocate a normal number of cells to the TE in chimeric embryos (Ralston and Rossant, 2008). Despite using the same gene knockout and RNAi approaches, these results are directly contradictory to those reported in other studies, which have shown that Cdx2 depletion compromises cell polarity and induces developmental arrest before the blastocyst stage, as well as significantly reducing blastocyst rate (the ability of zygotes to normally develop into blastocysts) (Jedrusik et al, 2010(Jedrusik et al, , 2015. One plausible explanation for this discrepancy could be the different genetic backgrounds among strains.…”
Section: Cdx2mentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, the total blastocyst formation rate did not decrease significantly with the maternal age. However, older women may have abnormally low levels of stored maternally transcribed mRNA, which is involved in trophectoderm function and maintenance of the blastocoel [Jedrusik et al 2010]. That might explain the lower good-morphology blastocyst rate in older women [Harton et al 2013].…”
Section: Discussionmentioning
confidence: 99%
“…1), the idea that localized maternal determinants are used in embryonic axial patterning remains controversial. For example, some studies, but not others, find evidence for a maternal role of gene products proposed to be maternal determinants (Cdx2) (55,56) in cell-fate specification in the embryo (57)(58)(59). Nevertheless, a significant body of data suggests that zygotic regulators and cell-cell interactions determine axis polarity and patterning in mammals (e.g., refs.…”
Section: Evolution Of Inheritance May Not Necessarily Depend On Its Ementioning
confidence: 99%